Motivating English Language Learners and Teachers in Indonesia - Imam Khasbani; Didin Nuruddin Hidayat (Linguists : Journal Of Linguistics and Language Teaching, 2020)
Motivation has been long believed to be an essential contributor to students’ success in learning English. Many studies (e.g., Gbollie & Keamu, 2017; Wang, 2008; Zhang & Xiao, 2006) have been dedicated to investigating the relationship between motivation and success in learning English. While these studies have contributed to shedding light on the importance of motivation on students’ achievement in learning English, insufficient research has been conducted to address the concept of motivation itself, how the concept has evolved since the first time it was developed, and to what extent motivation affects both teachers and students’ performances at school. Owing to this fact, the present article seeks to discuss the notion and conceptualization of motivation by following several steps. First, the present paper took on arguments from prominent figures on the field of motivation to explore the essence of motivation and why it is essential for English as second or foreign language (ESL/EFL) learning. The conversation then built on the current theoretical framework of types and factors influencing student and teacher motivation. Following that, a plethora of discussions on the possible ways to increase student and teacher enthusiasm and motivation inside EFL classrooms were elaborated.